2009
DOI: 10.1111/j.1466-7657.2009.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and mutual understanding: exchange experiences in Malawi for host and guest students

Abstract: Students experience both similarities and differences in practice, but similarities are regarded as the stronger impression. Learning relational skills is the primary learning outcome, but learning how to nurse patients is also an important outcome. During the exchange period all students developed cultural competence. This way of organizing shared placements for guest and host students from different countries is valuable for all students. It also met the curricular demands in both countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 14 publications
3
23
0
1
Order By: Relevance
“…27 This led to a common ethical dilemma between the nurse's obligation to start life-saving treatment and the patient's right to refuse. Chalanda 22 claimed that traditional beliefs and values in rural parts of Malawi influence the decision-making of patients and guardians.…”
Section: Discussionmentioning
confidence: 99%
“…27 This led to a common ethical dilemma between the nurse's obligation to start life-saving treatment and the patient's right to refuse. Chalanda 22 claimed that traditional beliefs and values in rural parts of Malawi influence the decision-making of patients and guardians.…”
Section: Discussionmentioning
confidence: 99%
“…2 All alumni we interviewed reported personal and professional outcomes comparable with those reported by others. [1][2][3][4][5][6][7][8][9][10][11][12][14][15][16][17][18] Nine of our participants, however, completed the international co-op experience 27 to 35 years before being interviewed, and all of them described the sustained influence of the experience on their personal and professional lives. Although this is a small number of participants, the time interval between the international experience and research interview was substantially longer than the intervals reported in other studies, the longest of which was 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…An international experience, particularly in low-resource (developing) countries, has been shown to increase self-reported outcomes such as self-confidence, 1-3 maturation, [3][4][5][6][7] ability to cope with risks and hardships, 2,7-9 insight into one's own culture through comparisons with the host culture, 7,10,11 and heightened appreciation for the economic prosperity in one's home country. 6,8,12 One study of international co-op for science and technology majors also showed that the co-op experience increased students' selfconfidence, language skills, and cultural understanding.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few researchers have conducted collaborative studies with other institutions to explore the experiences of participants and to provide a more in-depth analysis of the international program (Button, Green, Tengnah, Johansson, & Baker, 2005). In addition, several authors have described the development of cultural competence among students following participation in international exchange programs (Hagen, Munkhondya, & Myhre, 2009;Kuehn et al, 2011). However, there is a gap in the literature regarding the development of intercultural competencies among faculty members from different countries and institutions.…”
Section: Introductionmentioning
confidence: 99%